Biodegradable spunlace nonwoven fabric for wet wipes and method for manufacturing the same
Patent Information
- Application Number
- CN202510447506.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-10
AI Technical Summary
但这种可降解湿巾的柔软度仍有待提高,因为聚乳酸分子链具有较高的规整性和结晶度,这使得它本身具有一定的刚性,难以像木浆纤维那样在受到外力时轻易弯曲和变形
[0033] The spunlace nonwoven fabric raw material of the present invention includes a modified polylactic acid fiber obtained by blending quaternized polylactic acid containing quaternary ammonium salt side groups in the molecular structure with polylactic acid and melt spinning. The introduction of side groups can disrupt the regularity and orderly arrangement of polylactic acid molecular chains, weaken the interaction force between molecular chains, reduce crystallinity, improve the flexibility of polylactic acid fibers, and improve the softness of spunlace nonwoven fabric.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nonwoven fabric technology, specifically relating to a biodegradable wet wipe made of spunlace nonwoven fabric and its preparation method. Background Technology
[0002] With the continuous improvement of people's living standards and the enhancement of hygiene awareness, wet wipes, as a convenient and hygienic cleaning product, are increasingly widely used in daily life, covering multiple fields such as personal care, household cleaning, and healthcare. Spunlace nonwoven fabric, due to its excellent softness, absorbency, strength, and hand feel, has become an essential raw material for the production of wet wipes.
[0003] Traditional wet wipes made with spunlace nonwoven fabrics are mostly made from non-biodegradable synthetic fibers such as polyester and polypropylene. While these materials perform reasonably well, they are difficult to degrade in the natural environment and remain there long after disposal, causing serious "white pollution" to soil, water, and other ecological environments. With the increasing global awareness of environmental protection and the increasingly stringent environmental regulations, the development of biodegradable wet wipes using spunlace nonwoven fabrics is urgently needed.
[0004] Patent CN108286125B discloses a functional wet wipe with antibacterial and absorbent properties. This wipe is made of a multi-layered fiber web reinforced with hydroentangling, consisting of a carded fiber web, a modified hot-melt fiber web, a hot-rolled fiber web layer, and an absorbent fiber web. To reduce environmental impact, the carded and absorbent fiber webs are mostly made of biodegradable materials. However, the entanglement between the fiber web layers is poor, resulting in insufficient strength and easy damage during use, negatively impacting its antibacterial and absorbent properties. Patent CN112760810B discloses a biodegradable wet wipe production process and the wipe itself, along with a packaging film for the wipe. The raw materials include chitosan fiber and bamboo pulp fiber. It employs a mixed carding, cross-laying, hydroentangling, curing, and drying technique. The resulting base fabric not only overcomes the strength problems of the aforementioned patents but also saves on the use of antibacterial agents and preservatives due to the inherent antibacterial function of the non-woven fabric. However, the softness of these biodegradable wipes still needs improvement. Polylactic acid (PLA) molecular chains have high regularity and crystallinity, giving them a certain rigidity, making them difficult to bend and deform easily under external force like wood pulp fibers. During the hydroentangling process, wood pulp fibers orderly aggregate and arrange themselves around the rigid PLA short fibers to form a tight structure. While this structure helps improve the strength of the nonwoven fabric to some extent, it reduces its softness: it feels "hard" and "prickly" to the touch, its texture is more rigid and less smooth, affecting the user experience.
[0005] Therefore, it is necessary to develop a nonwoven fabric for biodegradable wet wipes that can meet both the strength and softness requirements of consumers. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a biodegradable wet wipe made from a spunlace nonwoven fabric and its preparation method. The raw material for the spunlace nonwoven fabric includes a modified polylactic acid fiber obtained by blending quaternized polylactic acid (PLA) containing quaternary ammonium salt side groups in its molecular structure with PLA and then melt spinning it. The introduction of the side groups disrupts the regularity and orderly arrangement of the PLA molecular chains, weakens the interaction forces between the molecular chains, reduces crystallinity, improves the softness of the PLA fibers, and enhances the softness of the spunlace nonwoven fabric. Seaweed fibers synergistically enhance the strength of the spunlace nonwoven fabric with the modified PLA fibers. Simultaneously, the synergistic effect of the seaweed fibers and modified PLA fibers in the raw material further strengthens the mechanical strength of the spunlace nonwoven fabric, enabling it to maintain excellent softness while possessing good mechanical properties.
[0007] To achieve the above objectives, the following technical solution is adopted:
[0008] A biodegradable wet wipe made of spunlace nonwoven fabric comprises the following raw materials in parts by weight: 40-50 parts wood pulp fiber, 20-30 parts modified polylactic acid fiber, 1-2.5 parts seaweed fiber, and 15-20 parts lyocell fiber;
[0009] The preparation steps of the modified polylactic acid fiber include:
[0010] 1) Modified polylactic acid is obtained by transesterification of alkyl aminobenzoate with polylactic acid with a number average molecular weight of 50,000-80,000.
[0011] 2) Modified polylactic acid reacts with 2,3-epoxypropyltrimethylammonium chloride to obtain quaternized polylactic acid;
[0012] 3) Quaternized polylactic acid is blended with polylactic acid with a number average molecular weight of 100,000-150,000 and then melt-spun.
[0013] The introduction of quaternary ammonium salt side groups into the polymer molecular chains of modified polylactic acid (PLA) fibers, due to the positive charge of these side groups, leads to electrostatic repulsion between molecular chains, hindering their orderly arrangement and reducing crystallinity. Furthermore, the steric hindrance effect of these side groups restricts localized movement of the polymer chains, interfering with the regular folding of chain segments during crystallization and further reducing crystallinity. While reduced crystallinity contributes to improved softness in spunlace nonwovens, it also negatively impacts their mechanical properties. PLA fibers significantly contribute to the mechanical properties of spunlace nonwovens; to compensate for the strength loss after modification, a suitable amount of seaweed fiber should be incorporated into the raw materials to ensure the overall strength of the spunlace nonwovens remains unaffected.
[0014] Algae fiber is a fiber made from alginate through spinning. It is more flexible and deformable than polylactic acid fiber. When an appropriate amount of algae fiber is entangled and overlapped with modified polylactic acid fiber during the hydroentangling process, the modified polylactic acid fiber can play its role in improving the softness of the hydroentangled nonwoven fabric while ensuring that the overall strength of the hydroentangled nonwoven fabric is not affected.
[0015] The mass ratio of the alkyl aminobenzoate to polylactic acid with a number average molecular weight of 50,000-80,000 is 3-5:100; the mass ratio of the 2,3-epoxypropyltrimethylammonium chloride to modified polylactic acid is 5-8:100; and the mass ratio of the quaternized polylactic acid to polylactic acid with a number average molecular weight of 100,000-150,000 is 10-15:100.
[0016] The alkyl aminobenzoate is selected from one or a combination of two or more of the following: dimethyl 2-aminoterephthalate, diethyl 2-aminoterephthalate, dimethyl 5-aminoisophthalate, diethyl 5-aminoisophthalate, dimethyl 4-aminoisophthalate, diethyl 4-aminoisophthalate, dimethyl 3-amino-phthalate, diethyl 3-amino-phthalate, and dimethyl 2-aminophthalate.
[0017] The modified polylactic acid fiber is 12-15 mm long and 1-2 dtex fine; the seaweed fiber is 30-40 mm long and 1.5-2 dtex fine; and the lyocell fiber is 7-10 mm long and 1-2 dtex fine.
[0018] Specifically, the modified polylactic acid fiber is prepared by a method comprising the following steps:
[0019] 1) Dissolve polylactic acid with a number average molecular weight of 50,000-80,000 in an organic solvent, add alkyl aminobenzoate and catalyst, and heat to reflux to react and obtain modified polylactic acid;
[0020] 2) Modified polylactic acid is dissolved in an organic solvent, 2,3-epoxypropyltrimethylammonium chloride is added and mixed well, and the mixture is heated to obtain quaternized polylactic acid;
[0021] 3) Quaternized polylactic acid and polylactic acid with a number average molecular weight of 100,000-150,000 are blended and melt-spun to obtain modified polylactic acid fiber.
[0022] In step 1), the organic solvent is selected from one or a combination of two or more of acetonitrile, chloroform, and 1,1,2-trichloroethane, preferably 1,1,2-trichloroethane. The catalyst is selected from one or a combination of two or more of tetrabutyl titanate, p-toluenesulfonic acid, and sodium formate. The amount of catalyst used is 1-3 wt% of the combined mass of polylactic acid and alkyl aminobenzoate with a number average molecular weight of 50,000-80,000. The reaction time is 10-18 hours. After the reaction, purification treatment is further included: adding alkaline solution, separating the liquid, and vacuum distilling the organic phase. The concentration of the alkaline solution is 15-20 wt%, and the alkaline solution is selected from one or a combination of two of sodium hydroxide solution and potassium hydroxide solution. The separating liquid is to remove the aqueous layer. The vacuum distillation is to remove the solvent.
[0023] In step 2), the organic solvent is selected from one or a combination of two or more of acetonitrile, chloroform, and 1,1,2-trichloroethane, preferably acetonitrile. The temperature is raised to 60-80°C, the reaction time is 3-8 hours, and the solvent is removed by vacuum distillation after the reaction is completed.
[0024] In step 3), the melt spinning employs a circular spinneret. The melt spinning process parameters are as follows: spinning temperature 225-255℃, winding speed 1700-1800m / min; drawing temperature 65-80℃, drawing ratio 2.8-3.2 times; heat setting temperature 100-120℃, heat setting time 1-3 minutes; crimping machine speed 2-2.5m / s, crimping wheel main pressure 0.25-0.35MPa, crimping wheel back pressure 0.06-0.1MPa, crimping temperature 60-90℃, number of crimps 5-25; cut length 7-10mm.
[0025] The wood pulp fibers are 1-4 mm long and 40-55 μm wide, and are selected from one or a combination of two or more of softwood pulp fibers and hardwood pulp fibers.
[0026] The present invention also provides a method for preparing the above-mentioned biodegradable wet wipes using spunlace nonwoven fabric, comprising the following steps:
[0027] Wood pulp fiber, modified polylactic acid fiber, lyocell fiber, and seaweed fiber are opened, mixed, carded, cross-laid, hydroentangled, dried, curled, sterilized, and slit to obtain a hydroentangled nonwoven fabric for biodegradable wet wipes.
[0028] The hydroentangling reinforcement is carried out in a rotary drum hydroentangling machine, which includes 4-6 hydroentangling passes, a hydroentangling pressure of 20-80 bar, and a water needle diameter of 0.1-0.3 mm.
[0029] The drying process involves drying in a vacuum drying oven at 100-120℃ for 2-5 hours.
[0030] The sterilization process involves ultraviolet irradiation.
[0031] The biodegradable wipes are made of spunlace nonwoven fabric with a basis weight of 50-80 g / m³. 2 .
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] The spunlace nonwoven fabric raw material of the present invention includes a modified polylactic acid fiber obtained by blending quaternized polylactic acid containing quaternary ammonium salt side groups in the molecular structure with polylactic acid and melt spinning. The introduction of side groups can disrupt the regularity and orderly arrangement of polylactic acid molecular chains, weaken the interaction force between molecular chains, reduce crystallinity, improve the flexibility of polylactic acid fibers, and improve the softness of spunlace nonwoven fabric.
[0034] In this invention, the seaweed fiber and modified polylactic acid fiber work synergistically to further enhance the mechanical strength of the spunlace nonwoven fabric, enabling it to maintain excellent softness while possessing good mechanical properties. Detailed Implementation
[0035] The present invention will be further described below with reference to specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, all "parts" mentioned in the embodiments of the present invention are parts by weight. All reagents used are commercially available in the art.
[0036] Polylactic acid with number average molecular weights of 50,000, 80,000, and 150,000 was purchased from Hubei Langbowan Biomedical Co., Ltd.
[0037] The hardwood pulp fiber was purchased from Hangzhou Xiangfu Wood Pulp Fiber Manufacturing Co., Ltd., with a length of 2.2 mm and a width of 42.1 μm.
[0038] Lyocell fiber was purchased from Baoding Swan New Fiber Manufacturing Co., Ltd., with a length of 10mm and a fineness of 1.7dtex.
[0039] The seaweed fibers with a length of 38mm and a fineness of 2dtex and a length of 30mm and a fineness of 1.5dtex were both purchased from Shaoxing Dan'ao Textile Co., Ltd.
[0040] Example 1
[0041] 1) Dissolve 100 kg of polylactic acid with a number average molecular weight of 50,000 in 200 L of 1,1,2-trichloroethane, add 5 kg of dimethyl 5-aminoisophthalate and 3 kg of p-toluenesulfonic acid, heat to reflux and react for 12 h, add 1 / 2 volume of 20 wt% sodium hydroxide solution of the resulting mixture, separate the liquid and remove impurities by vacuum distillation of the organic phase to obtain modified polylactic acid;
[0042] 2) Dissolve 100 kg of modified polylactic acid in 200 L of acetonitrile, add 8 kg of 2,3-epoxypropyltrimethylammonium chloride and mix well. Heat to 80 °C and react for 5 h. Remove the solvent by vacuum distillation to obtain quaternized polylactic acid.
[0043] 3) 15 kg of quaternized polylactic acid and 100 kg of polylactic acid with a number-average molecular weight of 150,000 were blended and melt-spun in a single-screw spinning machine using a circular spinneret to obtain modified polylactic acid fibers. The melt spinning process parameters were as follows: spinneret temperature set at 235℃ (spinning temperature), winding speed at 1800 m / min; drawing temperature at 80℃, drawing ratio at 2.8 times; heat setting temperature at 100℃, heat setting time at 3 minutes; crimping speed at 2.5 m / s, crimping wheel main pressure at 0.25 MPa, crimping wheel back pressure at 0.06 MPa, crimping temperature at 60℃, number of crimps at 12; and cutting length at 15 mm.
[0044] 4) 50 kg of hardwood pulp fiber, 30 kg of modified polylactic acid fiber, 20 kg of lyocell fiber, and 2.5 kg of seaweed fiber (38 mm in length, 2 dtex fineness) were opened, mixed, carded, cross-laid, and then sequentially hydroentangled in a rotary drum hydroentangler at pressures of 20 bar, 40 bar, 45 bar, 60 bar, 50 bar, and 45 bar (water needle diameter 0.12 mm). The fibers were then dried in a vacuum drying oven at 120°C for 3 hours, curled, sterilized by ultraviolet irradiation, and slit to obtain a weight of 50 g / m³. 2 Biodegradable wipes made from spunlace nonwoven fabric.
[0045] Example 2
[0046] The rest is the same as in Example 1, except that in step 4), the amount of modified polylactic acid fiber used is 20 kg.
[0047] Example 3
[0048] The rest is the same as in Example 1, except that in step 4), the amount of seaweed fiber used is 1 kg.
[0049] Example 4
[0050] The rest is the same as in Example 1, except that in step 3), the amount of quaternized polylactic acid used is 10 kg.
[0051] Example 5
[0052] The rest is the same as in Example 1, except that in step 2), the amount of 2,3-epoxypropyltrimethylammonium chloride used is 5 kg.
[0053] Example 6
[0054] The rest is the same as in Example 1, except that in step 1), the amount of dimethyl 5-aminoisophthalate used is 3 kg.
[0055] Example 7
[0056] The rest is the same as in Example 1, except that in step 1), 5-aminoisophthalate is replaced with an equal mass of 2-aminoterephthalate.
[0057] Example 8
[0058] The rest is the same as in Example 1, except that in step 4), the seaweed fiber specifications are 30 mm in length and 1.5 dtex in fineness.
[0059] Example 9
[0060] 1) Dissolve 100 kg of polylactic acid with a number average molecular weight of 50,000 in 200 L of 1,1,2-trichloroethane, add 3 kg of dimethyl 5-aminoisophthalate and 3 kg of p-toluenesulfonic acid, heat to reflux and react for 12 h, add 1 / 2 volume of 20 wt% sodium hydroxide solution of the resulting mixture, separate the liquid and remove impurities by vacuum distillation of the organic phase to obtain modified polylactic acid;
[0061] 2) Dissolve 100 kg of modified polylactic acid in 200 L of acetonitrile, add 5 kg of 2,3-epoxypropyltrimethylammonium chloride and mix well. Heat to 80 °C and react for 5 h. Remove the solvent by vacuum distillation to obtain quaternized polylactic acid.
[0062] 3) 15 kg of quaternized polylactic acid and 100 kg of polylactic acid with a number-average molecular weight of 150,000 were blended and melt-spun in a single-screw spinning machine using a circular spinneret to obtain modified polylactic acid fibers. The melt spinning process parameters were as follows: spinneret temperature set at 235℃ (spinning temperature), winding speed at 1800 m / min; drawing temperature at 80℃, drawing ratio at 2.8 times; heat setting temperature at 100℃, heat setting time at 3 minutes; crimping speed at 2.5 m / s, crimping wheel main pressure at 0.25 MPa, crimping wheel back pressure at 0.06 MPa, crimping temperature at 60℃, number of crimps at 12; and cutting length at 12 mm.
[0063] 4) 40 kg of hardwood pulp fiber, 20 kg of modified polylactic acid fiber, 30 kg of lyocell fiber, and 1 kg of seaweed fiber with a length of 30 mm and a fineness of 1.5 dtex were opened, mixed, carded, cross-laid, and then sequentially hydroentangled in a rotary drum hydroentangler at pressures of 20 bar, 40 bar, 45 bar, 60 bar, 50 bar, and 45 bar (with a water needle diameter of 0.12 mm). The fibers were then dried in a vacuum drying oven at 120°C for 3 hours, curled, sterilized by ultraviolet irradiation, and slit to obtain a weight of 50 g / m³.2 Biodegradable wipes made from spunlace nonwoven fabric.
[0064] Comparative Example 1
[0065] 1) 100 kg of polylactic acid (PLA) blend with a number-average molecular weight of 150,000 was melt-spun into PLA fibers using a single-screw spinning mill with a circular spinneret. The melt spinning process parameters were as follows: spinneret temperature set at 235℃ (spinning temperature), winding speed at 1800 m / min; drawing temperature at 80℃, drawing ratio at 2.8 times; heat setting temperature at 100℃, heat setting time at 3 minutes; crimping speed at 2.5 m / s, crimping wheel main pressure at 0.25 MPa, crimping wheel back pressure at 0.06 MPa, crimping temperature at 60℃, number of crimps at 12; and cutting length at 15 mm.
[0066] 2) 50 kg of hardwood pulp fiber, 30 kg of polylactic acid fiber, 20 kg of lyocell fiber, and 2.5 kg of seaweed fiber (38 mm in length, 2 dtex fineness) were opened, mixed, carded, cross-laid, and then sequentially hydroentangled in a rotary drum hydroentangler at pressures of 20 bar, 40 bar, 45 bar, 60 bar, 50 bar, and 45 bar (water needle diameter 0.12 mm). The fibers were then dried in a vacuum drying oven at 120°C for 3 hours, curled, sterilized by ultraviolet irradiation, and slit to obtain a yield of 50 g / m³. 2 Biodegradable wipes made from spunlace nonwoven fabric.
[0067] Comparative Example 2
[0068] The rest is the same as in Example 1, except that in step 4), the amount of seaweed fiber used is 0.5 kg.
[0069] Comparative Example 3
[0070] The rest is the same as in Example 1, except that in step 4), the amount of seaweed fiber used is 3 kg.
[0071] Comparative Example 4
[0072] The rest is the same as in Example 1, except that in step 2), 2,3-epoxypropyltrimethylammonium chloride is replaced with an equal mass of 1,2-epoxybutane.
[0073] The spunlace nonwoven fabrics prepared in the above embodiments and comparative examples were subjected to the following performance tests:
[0074] Tensile strength: Referring to standard GB / T 24218.3-2010 Textiles, Nonwovens, Test Methods, Part 3: Determination of breaking strength and elongation at break, the transverse tensile strength of the composite material in a wet state was tested using a YG028-500 tensile tester. The sample size was 50mm*500mm, the clamping distance was 200mm, and the tensile speed was 100mm / min.
[0075] Antibacterial properties: The bactericidal rate of the spunlace nonwoven fabric of this invention was tested according to the standard GB / T 15979-2024 Hygiene Requirements for Disposable Sanitary Products. The contact time was 5 minutes, and Escherichia coli was used as the test bacteria. The bactericidal rate was evaluated according to the following standards: Grade A: bactericidal rate ≥ 95%; Grade B: 95% > bactericidal rate ≥ 90%; Grade C: bactericidal rate < 90%.
[0076] Bending length: The test is conducted in accordance with the standard GB / T 18318.1-2009 Determination of bending properties of textiles. Bending length refers to the length of a rectangular fabric sample held at one end and suspended at the other end when it bends to 7.1° under its own weight. The smaller the bending length, the easier it is to bend and deform under its own weight, which means it is softer.
[0077] Table 1 Performance Test Results
[0078] Example 1 13.6 A 0.7 Example 2 14.2 B 1.2 Example 3 12.7 B 1.0 Example 4 13.9 B 0.8 Example 5 13.8 B 0.8 Example 6 13.8 B 1.0 Example 7 13.6 A 0.7 Example 8 13.1 A 0.7 Example 9 12.7 B 1.5 Comparative Example 1 12.5 C 1.9 Comparative Example 2 12.8 C 2.5 Comparative Example 3 14.9 A 3.2 Comparative Example 4 12.0 C 2.1
[0079] As can be seen from the performance test results in Table 1, the nonwoven fabric prepared by the present invention has excellent antibacterial properties and can achieve excellent softness without affecting the overall strength.
[0080] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.
Claims
1. A biodegradable wet wipe made of spunlace nonwoven fabric, characterized in that, It includes the following raw materials in parts by weight: 40-50 parts wood pulp fiber, 20-30 parts modified polylactic acid fiber, 1-2.5 parts seaweed fiber, and 15-20 parts lyocell fiber; The modified polylactic acid fiber is prepared by a method comprising the following steps: 1) Polylactic acid with a number average molecular weight of 50,000-80,000 is dissolved in an organic solvent, and alkyl aminobenzoate and catalyst are added. The mixture is heated to reflux to carry out transesterification reaction to obtain modified polylactic acid. 2) Modified polylactic acid is dissolved in an organic solvent, 2,3-epoxypropyltrimethylammonium chloride is added and mixed well, and the mixture is heated to obtain quaternized polylactic acid; 3) Quaternized polylactic acid and polylactic acid with a number average molecular weight of 100,000-150,000 are blended and melt-spun to obtain modified polylactic acid fiber.
2. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that, The mass ratio of the alkyl aminobenzoate to polylactic acid with a number average molecular weight of 50,000-80,000 is 3-5:100; the mass ratio of the 2,3-epoxypropyltrimethylammonium chloride to modified polylactic acid is 5-8:100; and the mass ratio of the quaternized polylactic acid to polylactic acid with a number average molecular weight of 100,000-150,000 is 10-15:
100.
3. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that... The alkyl aminobenzoate is selected from one or more combinations of 2-aminodimethyl terephthalate, 2-aminodiethyl terephthalate, 5-aminodimethyl isophthalate, 5-aminodiethyl isophthalate, 4-aminoisophthalate, 4-aminoisophthalate, 3-aminodimethyl terephthalate, 3-aminodiethyl terephthalate, and 2-aminodimethyl terephthalate.
4. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that... The modified polylactic acid fiber is 12-15 mm long and 1-2 dtex fine; the seaweed fiber is 30-40 mm long and 1.5-2 dtex fine; and the lyocell fiber is 7-10 mm long and 1-2 dtex fine.
5. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that... In step 1), the catalyst is selected from one or more of tetrabutyl titanate, p-toluenesulfonic acid, and sodium formate; the amount of the catalyst is 1-3 wt% of the combined mass of polylactic acid and alkyl aminobenzoate with a number average molecular weight of 50,000-80,000.
6. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that... In step 2), the organic solvent is selected from one or more combinations of acetonitrile, chloroform, and 1,1,2-trichloroethane; the temperature is raised to 60-80℃, the reaction time is 3-8h, and the solvent is removed by vacuum distillation after the reaction is completed.
7. The biodegradable wet wipes according to claim 6, made of spunlace nonwoven fabric, are characterized in that... In step 2), the organic solvent is selected from acetonitrile.
8. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that... In step 3), the melt spinning process parameters are as follows: spinning temperature is 225-255℃, winding speed is 1700-1800 m / min; drawing temperature is 65-80℃, drawing ratio is 2.8-3.2 times; heat setting temperature is 100-120℃, heat setting time is 1-3 minutes; crimping machine speed is 2-2.5m / s, crimping wheel main pressure is 0.25-0.35MPa, crimping wheel back pressure is 0.06-0.1MPa, crimping temperature is 60-90℃, number of crimps is 5-25; and cutting length is 7-10mm.
9. The biodegradable wet wipes according to claim 1, made of spunlace nonwoven fabric, are characterized in that, The wood pulp fibers are 1-4 mm long and 40-55 μm wide, and are selected from one or two types of softwood pulp fibers and hardwood pulp fibers.
10. The method for preparing the biodegradable wet wipes from the spunlace nonwoven fabric according to any one of claims 1-9, characterized in that, Includes the following steps: Wood pulp fiber, modified polylactic acid fiber, lyocell fiber, and seaweed fiber are opened, mixed, carded, cross-laid, hydroentangled, dried, curled, sterilized, and slit to obtain a hydroentangled nonwoven fabric for biodegradable wet wipes.
Citation Information
Patent Citations
A type of antibacterial and absorbent wet wipe
CN108286125B
A biodegradable wet wipe manufacturing process, wet wipes, and packaging film for the wet wipes.
CN112760810B
Fibers comprising starch and biodegradable polymers
CA2446092A1
Antibiotic polylactic acid fiber and preparation method thereof
CN105442308A